The nutritive value and role of Panicum turgidum Forssk. in the arid ecosystems of the Egyptian desert - Heneidy, Selim Z.; Halmy, Marwa Waseem (Acta Botanica Croatica, 2009)
Panicum turgidum is one of the most drought resistant plants in the Egyptian desert. Five habitat types were selected for the study: sand dunes (North Sinai and in Wady El-Natrun), gravel desert, coastal plain, and water runnels of a wadi bed (South Sinai and Eastern Desert). About 47.4% of the studied sites were subjected to high grazing pressure, 26.3% to moderate grazing pressure; the remaining 26.3% were subjected to low grazing pressure. Concentration of the nutrients (K, Na, Ca, P and Ca/P ratio) in the grazeable parts of P. turgidum populations exhibited insignificant variability between habitats and phytogeographical regions. Meanwhile, concentration of potassium showed significant variability between the phytogeographical regions. Ca/P ratio of the grazeable parts of P. turgidum was significantly related to the soil silt and organic matter content. The percentage of crude protein was higher than the minimum required for the maintenance of the grazing animals, i.e. P. turgidum has a good or excellent forage quality. Due to its high nutritive value and ease of cultivation, P. turgidum grains could be considered as a potential crop, which may serve as a supplementary food to the common cereals. It worth noting that the variation in the nutritive values among the cultivated populations was insignificant as all the cultivated populations had a high nutritive value, indicating the effect of edaphic factors on the wild population nutritive value which was proved also from the correlation between the edaphic factors and nutritive variable.